Do patellar degeneration and obesity have an impact on anterior knee pain in total knee arthroplasty without patellar resurfacing? - Haberal, Bahtiyar; Kaya Simsek, Ekin; Sahin, Orcun; Ersozlu, Salim (Annals of Medical Research, 2021)
Aim: Purpose of this study was to determine clinical and radiological outcomes of total knee arthroplasty (TKA), and analyze correlation between the degree of the patellar degeneration and anterior knee pain.Materials and Methods: We identified all patients at our institution underwent TKA between January 2009 and March 2011. Patients were classified into two groups according to Outherbridge classification system. The effect of patellar resurfacing on clinical and radiological outcomes was evaluated. Results: A total of 326 patients were included in the present study. The female to male ratio was 254/72. The preoperative, early postoperative and last follow-up range of motion, Knee Society Score and functional scores were similar between groups (p=0.707, p=0.241, p=0.123, p=0.864, p=0.212, p=0.320, p=0.966, p=0.117, p=0.232, respectively). Patient satisfaction rates were similar between groups at last follow-up (p=0.127). Conclusion: In the present study there is no significant relationship between the severity of the patellar cartilage defect and clinical/radiological outcomes at long-term follow-up. Therefore, we do not suggest resurfacing the patella in the surgical treatment of knee osteoarthritis to decrease knee pain and improve knee functionality.